Synthesis and structure of salts of 2-(((3-mercapto-5-methyl-4H-1,2,4-triazole-4-yl)imino)methyl)benzoic acid - T. V. Hlazunova (Zaporozhye State Medical University, 2020)
Modern pharmacy and medicine can offer a substantial number of highly effective synthetic medicines. A great portion of these medicines falls into the group of 1,2,4-triazole derivatives. 1,2,4-Triazoles are distinguished by important pharmacological properties, including antimicrobial, antifungal, anti-inflammatory, hypoglycemic, while also being capable of stimulating the central nervous system. Undoubtedly, a constant increase of number of publications regarding the synthesis, characterization of biological, chemical, and physical properties of 1,2,4-triazole derivatives by both foreign and Ukrainian researchers promotes the search for promising compounds of this class of heterocyclic compounds globally. The purpose of our work was to synthesize and characterize structures of salts of 2-(((3-mercapto-5-methyl-4H-1,2,4-triazole-4-yl)imino)methyl)benzoic acid, as potentially bioactive compounds. Materials and methods. The physical-chemical characterization of the synthesized compounds was conducted according to the guidelines provided by the State Pharmacopoeia of Ukraine. The melting point was determined using MPA100 apparatus. Elemental analysis was held using Elementar Vario L.cube analyzer. 1H NMR spectra were recorded using Varian Mercury VX-200 spectrometer (1Н, 200 MHz). Chromatographic and mass-spectrometric data were obtained using Agilent 1260 Infinity LC system coupled with Agilent 6120 mass spectrometer. Results and discussion. 2-(((3-Mercapto-5-methyl-4H-1,2,4-triazole-4-yl)imino)methyl)benzoic acid was used as the starting compound for the synthesis of the new structures. In order to afford the desired compounds, the starting material was subjected to salt formation reactions with ammonium hydroxide, sodium and potassium hydroxides, methylamine, ethylamine, dimethylamine, 1-propylamine, 2-propylamine, monoethanolamine, diethylamine, tert-butylamine, piperidine, piperazine, morpholine, 2-methylpiperidine, and 4-methylmorpholine whether in alcohol or water solutions. Conclusions. The chemical experiments resulted in 16 new substances, salts of 2-(((3-mercapto-5-methyl-4H-1,2,4-triazole-4-yl)imino)methyl)benzoic acid. The chemical structure of the synthesized compounds was confirmed using instrumental methods, including 1H NMR spectroscopy, LC-MS, and elemental analysis. The obtained salts will be used in further pharmacological research.